At high level dialogue, Stakeholders Rally Support for Women’s Empowerment in Agriculture - National update (National Update, 2024)
The Consultative Group on International Agricultural Research (CGIAR) Gender Equality Initiative, through its HER+ initiative, has emphasized the urgent need for improved access to agricultural land and resources for women. This call to action was made during a high-level dialogue held on October 9, 2024, in Abuja, aimed at addressing barriers women face in Nigeria’s agrifood sector. The dialogue served as a platform for stakeholders from government, civil society, and academia to collaborate on innovative approaches that recognize women as essential agents of change in agriculture.